Modules for laboratory and field develop content area learning science, technology and environment in college “Juan José Crespo y Castillo” de Huancapallac. Huánuco - 2012 - Flores Manrrique, Ayar (2017)
The research aims to determine the influence of the use of the modules and field laboratory to develop learning content Area Science, Technology and Environment in secondary students of School “Juan José Crespo y Castillo” of Huancapallac. The methodology includes: workspace recognition, diagnosis and current status of the laboratory modules, development activities and field laboratory, and training course aimed at secondary teachers. The population consists of 34 students of the first, second and fourth grade school. The sample consists of 34 students assisted the first, second and fourth grade school. Through this paper manages to develop learning content: conceptual, procedural and attitudinal.